Organizational Control Systems and Pay-for-Performance in the Public Service - Bruno S. Frey; Fabian Homberg; Margit Osterloh (Center for Research in Economics, Management and the Arts (CREMA), 2013)
Under certain conditions, output related performance measurement and pay-for-performance produce negative outcomes. We argue that in public service, these negative effects are stronger than in the private sector. We combine Behavioural Economics and Management Control Theory to determine under which conditions this is the case. We suggest as alternatives to the dominant output related pay-for-performance systems selection and socialization, exploratory use of output performance measures, and awards.
Keywords: 330; organization control; organizational forms; public administration; organizations; public service motivation